Authorship and the production of literary value, 1982-2012: Bret Easton Ellis, Paul Auster, JT LeRoy, and Tucker Max. - Lutton, A (2014)
Definitions of celebrity authorship and material textuality at the turn of the twenty-first century have predominantly emphasised the implicitly negative aspects of contemporary developments in the literary marketplace. Particularly prominent are arguments that the practice of authorship has become subject to homogenisation by the matrix of celebrity in which successful writers are now expected to function; and, further, that the changing nature of texts themselves and the ways in which they are marketed is eroding the implicitly superior position traditionally held by literature in the cultural marketplace. This thesis views such readings as pessimistic, and offers an alternative, seeking to formulate a new critical approach to literary value in the contemporary sphere which would appreciate notions of celebrity, populism, and digital mediation as integral and productive aspects of how literary value is formed today. Through in-depth focus on the cases of a number of unconventional contemporary American authors whose work demonstrates differing, innovative approaches to the process of authorship, this thesis exposes the ways in which contemporary, atypically ‘literary’ instances of writing can and do work within and develop beyond traditional conceptualisations of authorship and literary value. Bret Easton Ellis and Jay McInerney, largely critically considered prototypical ‘celebrity’ authors, are in the first chapter reconsidered as writers whose understanding of their position within the literary marketplace affords them a self-conscious, critical perspective on the notion of celebrity in their work and public personae. The productively self-conscious author-figure is reconsidered in the second chapter, which reads the individual and joint works of author Paul Auster and visual artist Sophie Calle as foregrounding the process of creative collaboration as uniquely illuminating and transformative within the contemporary literary sphere. The notion of dual authorship is revisited and reconceptualised in the third chapter, which considers JT LeRoy and the practice of hoax authorship, outlining how this process forces the reformulation of literary value, particularly in a contemporary setting in which authors are accountable for their work in newer, more visible ways. The final chapter expands these previously-introduced themes to consider bloggers-turned-authors, particularly Tucker Max and Julie Powell, and the impact of the merging of old and new textualities on both the orientation of the figure of the writer and the way in which value is attached to his texts by readers. Ultimately, the unconventional nature of these examples is shown to belie the universality of the representations of value they enact, contributing to a full and salient account of how literary value is determined at the beginning of the twenty-first century.